The Roman clan the gens from ancient ideology to modern anthropology - Smith, Christopher 1965- (The W.B. Stanford memorial lectures, 2006)
The gens, a key social formation in archaic Rome, has given rise to considerable interpretative problems for modern scholarship. In this comprehensive exploration of the subject, Professor Smith examines the mismatch between the ancient evidence and modern interpretative models influenced by social anthropology and political theory. He offers a detailed comparison of the gens with the Attic genos and illustrates, for the first time, how recent changes in the way we understand the genos may impact upon our understanding of Roman history. He develops a concept of the gens within the interlocking communal institutions of early Rome, which touches on questions of land ownership, warfare and the patriciate, before offering an explanation of the role of the gens and the part it might play in modern political theory. This significant work makes an important contribution not only to the study of archaic Rome, but also to the history of ideas